REFLEXIVIDADE, INICIAÇÃO, SABERES: EXEMPLO DE UMA PESQUISA EM UM “CLUBE DE PAIS” EM SEINE SAINT-DENIS | Reflexivity, initiation, knowledge: example of research on a “Parents Club” in Seine Saint-Denis (Trabalho & Educação, 2016)
In the humanities and social sciences, reflexivity is often cited but rarely incorporated and effective. It is, at best, limited to a monitoring function or methodological considerations, separated from actual scientific results. I would like to break away from this practice in order to enhance the heuristic potential of the reflexive knowledge of anthropology. When resuming the communication phenomenon that connects the observer to the observed and, more specifically, when reviewing the communication anomalies, it becomes possible, on one hand, to favor a unique introduction to the suffering of others and, on the other, to produce a specific field of knowledge from the issues raised. ___